The Idea of Biblical Interpretation : essays in honor of James L. Kugel - Kugel, James L.; Najman, Hindy; Newman, Judith H. (Judith Hood), 1961- (Leiden ; Boston : Brill, 2004)
Biblical and literary scholars explore themes central to the work of Kugel (classical and modern Jewish and Hebrew literature, Harvard U. and Bible, Bar Ilan U., Israel), who enlarged the field of biblical studies from a narrow focus on the origins and prehistory of the biblical texts to encompass the emergence of Scripture and its role in shaping.
pt. 1. The Bible as it was. The conversion of Abraham to Judaism, Christianity, and Islam / Jon D. Levenson -- The alleged "hidden light" / Jacob Milgrom -- Golden calf stories: the relationship of Exodus 32 and Deuteronomy 9-10 / Christine E. Hayes -- Plumbing the depths: genre ambiguity and theological creativity in the interpretation of Psalm 130 / Harry P. Nasuti -- [Kol ha-adam] and the evaluation of Qohelet's Wisdom in Qoh 12:13, or, "The 'A is so, and what's more, B': theology of Ecclesiastes" / Peter Enns -- The symbolic significance of writing in ancient Judaism / Hindy Najman -- pt. 2. Traditions of the Bible in Second Temple Judaism. Seven mysteries of knowledge: Qumran E/sotericism recovered / Elliot R. Wolfson -- The contribution of the Qumran discoveries to the history of early biblical interpretation / Moshe J. Bernstein -- Myth, history, and mystery in the Copper scroll / Steven P. Weitzman -- The concept of covenant in the Qumran scrolls and rabbinic literature / Lawrence H. Schiffman -- Open and closed eyes in the Animal apocalypse (1 Enoch 85-90) / James C. VanderKam -- Before the fall: the earliest interpretations of Adam and Eve / John J. Collins -- The democratization of kingship in Wisdom of Solomon / Judith H. Newman -- pt. 3. The interpretive life of biblical texts from early Judaism to the present. Two powers in heaven; or, The making of a heresy / Daniel Boyarin -- Iterated quotation formulae in Talmudic narrative and exegesis / Bernard Septimus -- Moses and the commandments: can hermeneutics, history, and rhetoric be disentangled? / Steven D. Fraade -- The Alphabet of Ben Sira and the early history of parody in Jewish literature / David Stern -- Does Rashi's Torah commentary respond to Christianity? A comparison of Rashi with Rashbam and Bekhor Shor / Shaye J.D. Cohen -- Rashi and Ibn Ezra on the Hitpael: Peshat in the medieval disputes of Hebrew grammar / Isaiah Teshima -- Paradise lost and traditional exegesis / Lawrence F. Rhu -- A Nazi New Testament professor reads his Bible: the strange case of Gerhard Kittel / Wayne A. Meeks -- The hermeneutical significance of Emmanuel Levinas's Talmudic readings / Gerald L. Bruns.
Includes bibliographical references and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Bible. -- Criticism, interpretation, etc; Dead Sea scrolls; Bible. -- Criticism, interpretation, etc., Jewish; Bible. -- Critique, interprétation, etc. juives; Bible; Dead Sea scrolls; Rabbinical literature -- History and criticism; Littérature rabbinique -- Histoire et critique; RELIGION -- Biblical Criticism & Interpretation -- Old Testament; Rabbinical literature; Criticism, interpretation, etc; Festschriften; Festschriften